Respon Masyarakat terhadap Kepemimpinan Kepala Desa dan Kepala Kelurahan di Lembang Parang Kabupaten Gowa - Amal Nur; Armin Arsyad; Gustiana Anwar Kambo (Palita: Journal of Social Religion Research, 2023)
This paper describes the leadership of the village head. Community response is a benchmark for running an administration in Lembang Parang. The method used in this paper is qualitative research that uses primary data sources by direct observation by the author in Lembang Parang Village, Barombong District, Gowa Regency. Researchers collect data and information through interviews with related parties. This research is supported by data sources and information from books and documents that help research themes, journals, and electronic information media. The results of the study show that the transactional efforts used by the leadership of the Village Head towards his constituents are effective by observing the community's enthusiasm in actively participating in Village programs. The people of Lembang Parang received Transactional Leadership from Mursalim Abubaedah. On the other hand, the transformational leadership pattern implemented by Fatmawati as Lurah was also well received by the people of Lembang Parang. For the people of Lembang Parang, the transformational design implemented by Fatmawati is seen as an effort to improve people's lives in Lembang Parang.